2014
DOI: 10.1016/j.ijdevneu.2014.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to integerrimine N‐oxide impaired the maternal care and the physical and behavioral development of offspring rats

Abstract: Plants that contain pyrrolizidine alkaloids (PAs) have been reported as contaminants of pastures and food, as well as being used in herbal medicine. PAs are responsible for poisoning events in livestock and human beings. The aim of this present study was to evaluate effects of prenatal exposure to integerrimine N-oxide, the main PA found in the butanolic residue (BR) of Senecio brasiliensis, on both physical and behavioral parameters of Wistar rat offspring. The toxicity and maternal behavior were also evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 65 publications
(86 reference statements)
2
9
0
6
Order By: Relevance
“…Open‐field testing is commonly used to measure behavioral responses, such as locomotor activity (Patti et al, 2005), hyperactivity (Fukushiro et al, 2008), exploratory behavior and anxiety (Prut and Belzung, 2003). In our previous study, no alterations in open‐field behavior during infancy were observed (Sandini et al, 2014). However, in the present study, we observed that male rats that were treated prenatally with 9 mg/kg integerrimine N‐oxide showed increased locomotion in adulthood.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Open‐field testing is commonly used to measure behavioral responses, such as locomotor activity (Patti et al, 2005), hyperactivity (Fukushiro et al, 2008), exploratory behavior and anxiety (Prut and Belzung, 2003). In our previous study, no alterations in open‐field behavior during infancy were observed (Sandini et al, 2014). However, in the present study, we observed that male rats that were treated prenatally with 9 mg/kg integerrimine N‐oxide showed increased locomotion in adulthood.…”
Section: Discussionmentioning
confidence: 63%
“…PAs are generally hepatotoxic, and there is some evidence that integerrimine N‐oxide can cause neurotoxic effects in vivo (Gimmeler, 1986; Sandini et al, 2014). Thus, we investigated possible alterations in the central nervous system in rats during adulthood because our previous studies showed that this treatment can cause alterations in maternal behavior and impair the physical development of offspring (Sandini et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations